Diurnal fluctuations of secondary photooxidants in air and of detoxification systems in the foliage of Mediterranean forest trees - Junkermann, Wolfgang; Polle, A. (Atmospheric Environment, 1997)
s-phase peroxide mixing ratios were measured in the canopy area of a Mediterranean oak/pine fo.rest. Concurrently the activities of cell wall localized peroxidases, which protect leaves from external oxidants, were investigated. The diurnal cycles of peroxidase activity showed a strong decrease when the gas-phase concentration of highly phytotoxic hydroxy hydroperoxides increased. These results suggest that ambient gas-phase mixing ratios of organic peroxides may injure the plants’ oxidative defence system
Keywords: antioxidant protection; organic peroxides; peroxidase activity

Diurnal fluctuations of secondary photooxidants in air and of detoxification systems in the foliage of Mediterranean forest trees (Atmospheric Environment, 1997)
s-phase peroxide mixing ratios were measured in the canopy area of a Mediterranean oak/pine fo.rest. Concurrently the activities of cell wall localized peroxidases, which protect leaves from external oxidants, were investigated. The diurnal cycles of peroxidase activity showed a strong decrease when the gas-phase concentration of highly phytotoxic hydroxy hydroperoxides increased. These results suggest that ambient gas-phase mixing ratios of organic peroxides may injure the plants’ oxidative defence system